DIGNITARIAN REVOLUTION OF THE TWENTIETH CENTURY - PATSURKIVSKYY, PETRO; HAVRYLYUK, RUSLANA (Ehrlich’s Journal, 2023)
In this paper we explore the process of emerging and further affirmation of human dignity as a transcendental value of an individual and constitutive principle of human rights. We make this using anthroposociocultural approach and its corresponding cognitive methods. We argue that dignitarian revolution became one of the most important and most influential global events of the twentieth century and might be counted among the greatest achievements of the Western civilization and humankind in general. Its quintessence is the developing of understanding of human dignity as the main universal transcendental value of human personality and the constitutive principle of human rights. We defend the claim that abovementioned understanding of human dignity is grounded in the jus-naturalistic perception of human nature firstly, as identical for everyone, and, secondly, as being the dual in each person, organically combining bio-psychophysiological (individual) and anthroposociocultural (social) basic elements. Such perception of human nature is a consequence of the understanding of human needs as transcendental ones. The new paradigm of human dignity has found its most complete and adequate embodiment within the legal matrix of the doctrine of dignitarian constitutionalism.